IF JESUS IS GOD IN THE FLESH, WHY DID HE NOT KNOW HIS COMING: MARK 13:32 - Woy, Jones Ted Lauda; Sepang, Douglas Edward (Klabat Theological Review, 2025)
This study explores the Christological and theological significance of Mark 13:32, where Jesus states that the timing of His return is known only by the Father. Mark 13, the Gospel's longest discourse, presents an apocalyptic vision centered on the destruction of the temple and final judgment. Scholars highlight the disciples’ reverence for the temple and Jesus’ prophetic response, linking historical events with eschatological hope. The passage raises critical questions regarding Jesus’ divine and human knowledge. Through a Historical-Grammatical analysis, this research clarifies the theological implications of Christ’s dual nature, offering insights relevant to pastors, church leaders, and theological studies. Keywords: Christological, Theological, Judgment, and Temple.